Attitude Of Technology And Their Impact On Interest Of Internet Banking - DEWI, I Gusti Ayu Ratih Permata (PT Keberlanjutan Strategis Indonesia, 2021)
This study aims to determine the effect of perceived benefits, ease of use and trust in the attitude of using technology and its impact on the intention to use Internet Banking (Empirical Study: Customers of PT. Bank Rakyat Indonesia Tbk, Gianyar Branch). PT. Bank Rakyat Indonesia Tbk as one of the largest banks with branches in every city and units in almost every sub-district level, has become one of the banks used as customers to make savings and loans and other transactions. The data used are primary data. D ata primary obtained from questionnaires distributed to the Customer PT. Bank Rakyat Indonesia Tbk Gianyar Branch. The data analysis technique used is regression analysis multiple linear . The results showed that perceived usefulness, ease of use and trust had an effect on attitudes towards technology use. Furthermore, the attitude of using technology affects the interest in repeated use of internet banking.